Agonistics thinking the world politically - Mouffe, Chantal (Verso, 2013)
Political conflict in our society is inevitable, and the results are often far from negative. How then should we deal with the intractable differences arising from complex modern culture? Developing her groundbreaking political philosophy of agnostics--the search for a radical and plural democracy--Chantal Mouffe examines international relations, strategies for radical politics, the future of Europe and the politics of artistic practices. She shows that in many circumstances where no alternatives seem possible, agonistics offers a new road map for change. Engaging with cosmopolitanism, post-operaism, and theories of multiple modernities she argues in favor of a multipolar world with a real cultural and political pluralism. -- Publisher.